2012
DOI: 10.1159/000343469
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Fat Transfer in a Patient with Lupus Erythematosus Profundus

Abstract: Lupus erythematosus profundus, a form of chronic cutaneous lupus erythematosus, is a rare inflammatory disease involving in the lower dermis and subcutaneous tissues. It primarily affects the head, proximal upper arms, trunk, thighs, and presents as firm nodules, 1 to 3 cm in diameter. The overlying skin often becomes attached to the subcutaneous nodules and is drawn inward to produce deep, saucerized depressions. We present a rare case of lupus erythematosus profundus treated with autologous fat transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…suggested that the autologous fat transfer is a good choice to correct face atrophic lesions in patients with lupus erythematosus. Unquestionable advantages of this method are that the material used is patients’ own tissue (biocompatible), it has no allergic reaction and is easy to harvest [ 15 ]. A similar treatment path was introduced in the first described patient.…”
Section: Discussionmentioning
confidence: 99%
“…suggested that the autologous fat transfer is a good choice to correct face atrophic lesions in patients with lupus erythematosus. Unquestionable advantages of this method are that the material used is patients’ own tissue (biocompatible), it has no allergic reaction and is easy to harvest [ 15 ]. A similar treatment path was introduced in the first described patient.…”
Section: Discussionmentioning
confidence: 99%
“…Successful fat transfer has been reported in both lupus panniculitis and DLE (Table 4). 1,40–47 Complications from the procedure are rare but can include fat necrosis requiring drainage, as seen in one case report 45 . Adequate control of the underlying inflammatory disease prior to fat transfer may help facilitate optimal results.…”
Section: Methodsmentioning
confidence: 99%